(untitled) (Global Journal of Human-Social Science, 2023)
A man’s shirt, made during the mid 1950’s, whose evidence of having existed is a family portrait is the trigger, in this very article, of observations about the ingeniosity surrounding the daily and domestic production of those objects that result from and on the materiality of the common person history and, therefore, in the idea of the construction of thought in Design.